Extended TAM model to explore the factors that affect intention to use AI robotic architects for architectural design. Issue 3 (4th March 2022) - Lin, Chen-Yang; Xu, Ni
ABSTRACT: The development of artificial intelligence (AI) made human feel the pressure of machine competition. The architectural industry focuses on whether the AI will replace manpower. This study is an exploratory one. The problems that AI will have in the practice of architectural design are discussed through semi-structured interviews with architects, draftsmen, drawing reviewers, construction company owners, and professors of architecture. This study proposes an extended robotic architectural technology acceptance model with five facets and ten elements. This model highlights two dimensions, namely, specialised field diversity and controllable flexibility. This study provides new three implications in the future, namely, development direction, theoretical framework, and industry guidance, in the architectural design with artificial intelligence. Diversity and flexibility are important research directions for the development of AI robotic architects, just as fluctuations phenomenon in human capabilities can lead to a mutation effect in the design. Human beings need to contribute their own emotional intelligence, and replace competitive relationship with complementary mode of extended intelligence. Similar to any new technology, AI may create many jobs no less than it replaces.